Histones, Their Variants and Post-translational Modifications in Zebrafish Development - Cavalieri, Vincenzo (Frontiers in Cell and Developmental Biology, 2020)
Complex multi-cellular organisms are shaped starting from a single-celled zygote, owing to elaborate developmental programs. These programs involve several layers of regulation to orchestrate the establishment of progressively diverging cell type-specific gene expression patterns. In this scenario, epigenetic modifications of chromatin are central in influencing spatiotemporal patterns of gene transcription. In fact, it is generally recognized that epigenetic changes of chromatin states impact on the accessibility of genomic DNA to regulatory proteins. Several lines of evidence highlighted that zebrafish is an excellent vertebrate model for research purposes in the field of developmental epigenetics. In this review, I focus on the dynamic roles recently emerged for histone post-translational modifications, histone modifying enzymes, histone variants and histone themselves in the coordination between the precise execution of transcriptional programs and developmental progression in zebrafish. In particular, I first outline a synopsis of the current state of knowledge in this field during early embryogenesis. Then, I present a survey of histone-based epigenetic mechanisms occurring throughout morphogenesis, with a stronger emphasis on cardiac formation. Undoubtedly, the issues addressed in this review take on particular importance in the emerging field of comparative biology of epigenetics, as well as in translational research.